THU0498 PATIENT-REPORTED TREATMENT BURDEN AND ITS IMPACT ON QUALITY OF LIFE IN JUVENILE IDIOPATHIC ARTHRITIS: RESULTS FROM THE PHARMACHILD REGISTRY. (2nd June 2020) - Alongi, A.; Consolaro, A.; Vijatov-Djuric, G.; Filocamo, G.; Vougiouka, O.; Olivieri, A. N.; Herrera Mora, C.; Emminger, W.; Ravelli, A.; Ruperto, N.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) patients experience impaired health and wellbeing due to multiple causes of physical and psychosocial distress, including treatment burden. Despite emerging evidence of its relevance [1], the contribution of treatment adverse events to patient-reported outcomes (PROs) in JIA has been poorly explored. Objectives: To evaluate and rank the impact of patient-reported adverse events (AEs) on overall wellbeing, health-related quality of life (HRQoL), school problems and self-reported medication adherence using data from Pharmachild, a large international JIA pharmacovigilance registry. Methods: Registry entries on 5340 prospective visits of 2251 patients enrolled till December 2018 were analyzed; all included patients were treated with at least one DMARDS or Biologic agent at the time of visit. In the Juvenile Arthritis Multidimensional Assessment Report (JAMAR), patients and parents compiled a checklist of treatments, side effects, self-reported adherence, administration difficulties and disease-related school problems occurred in the previous 4 weeks. Evaluated outcomes included patient acceptable symptom state (PASS), VAS-measured patient assessment of overall wellbeing (PGA) and HRQoL, assessed through the physical health (PhH) and psychosocial health (PsH) subscales. The relationships between AEs and PROs were tested through generalized linear models, accounting for disease activity and symptoms levels. Bayesian Networks were used to explore the causal effects of specific AEs on outcomes to disentangle the confounding role of disease status. Results: AEs were reported in 22.9% of visits. For similar levels of physician global assessment (MD global), patient-assessed disease activity, pain and function, patients reporting AEs had worse PGA, PsH, and lower probability of reaching PASS (fig. 1, all p-values <0.001). The impact of AEs on PGA was small but not trivial (effect size η 2 0.031) and appears to be mediated by effects on PsH and school problems (p <0.001). Non-linear regression modelling revealed a significant moderating effect of MD global levels < 2.5 on the relationship between AEs and PGA (p 0.003), indicating that the impact of AEs is higher for lower disease activity states. AEs predicted self-reported medication adherence (p<0.001), even when adjusted for the number of administered treatments. In the Bayesian network model, mood swing and sleep problems emerged as the most influential items affecting PsH, (respectively, total effect 2.62 and 1.25, both p< 0.001). Fig. 2 shows the total standardized effect of specific AEs on mean PsH levels. Nausea had the highest impact on treatment adherence (total effect -0.0541, p <0.001), being the only AE directly linked to drug refusal. Conclusion: AEs have a measurable effect on the wellbeing and psychosocial health of JIA patients, particularly when disease activity is low, and significantly affect school activity and medication adherence. Mood swings and sleep problems show the strongest influence on HRQoL. Addressing AEs appears important to reduce disease impact, improve patients' satisfaction and therapeutic compliance. References: [1]Weitzman, Elissa R., et al. Journal of patient-reported outcomes 2.1 (2018): 1. Acknowledgments: for the Paediatric Rheumatology International Trials Organisation (PRINTO) Disclosure of Interests: Alessandra Alongi: None declared, Alessandro Consolaro Grant/research support from: Pfizer Inc., AlfaSigma, Speakers bureau: AbbVie, Gordana Vijatov-Djuric: None declared, Giovanni Filocamo: None declared, Olga Vougiouka: None declared, Alma Nunzia Olivieri: None declared, Cristina Herrera Mora: None declared, Wolfgang Emminger: None declared, Angelo Ravelli: None declared, Nicolino Ruperto Grant/research support from: Bristol-Myers Squibb, Eli Lily, F Hoffmann-La Roche, GlaxoSmithKline, Janssen, Novartis, Pfizer, Sobi (paid to institution), Consultant of: Ablynx, AbbVie, AstraZeneca-Medimmune, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Eli Lily, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, Sanofi, Servier, Sinergie, Sobi, Takeda, Speakers bureau: Ablynx, AbbVie, AstraZeneca-Medimmune, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Eli Lily, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, Sanofi, Servier, Sinergie, Sobi, Takeda